Space technology intervention in rural development - Kundan Kumar; Sujan, D.K.; Mishra, B.P. (2006)
Space technology of India is one of the fastest growing technologies in the world. It has given a fillip to the development of communication and remote sensing technology in India. Due to lack of fund and infrastructure facility, space technology application for rural development is a bit slow but it may not be a constraint in future. There is a great scope and prospect of space technology's future to move rural India on the path of development. - Reproduced.
Keywords: Rural development; Space technology